Nighttime eating during pregnancy and infant adiposity at 6 months of life - Rodríguez-Cano, Ameyalli M.; Medel-Canchola, Berenice; González-Ludlow, Isabel; Rodríguez-Hernández, Carolina; Reyes-Muñoz, Enrique; Schiffman-Selechnik, Esther; Estrada-Gutierrez, Guadalupe; Perichart-Perera, Otilia (Frontiers in Nutrition, 2024)
Chrononutrition studies the relation between diet, circadian rhythms and metabolism, which may alter the metabolic intrauterine environment, influencing infant fat-mass (FM) development and possibly increasing obesity risk. Aim: To evaluate the association of chrononutrition in pregnancy and infant FM at six months. Methods: Healthy pregnant women and term-babies (n=100pairs) from the OBESO cohort (2017-2023) were studied. Maternal registries included pregestational body-massindex (BMI), gestational complications/medications, weight gain. Diet (three 24hour-recalls, 1 each trimester) and sleep-schedule (first and third trimesters) were evaluated computing fasting (hours from last-first meal), breakfast and dinner latencies (minutes between wake up-breakfast and dinnersleep, respectively), number of main meals/day, meal skipping (≥1main meal/d on three recalls) and nighttime eating (from 9:00pm-5:59am on three recalls). Neonatal weight, length, BMI/age were assessed. At 6 months, infant FM (kg, %; air-displacement plethysmography) was measured, and FM index (FMI -kgFM/length 2 ) computed. Exclusive breastfeeding (EBF) was recorded. Multiple linear regression models evaluated the association between chrononutrition and 6-month infant FM. Results: Mean fasting was 11.7±1.3 hrs; breakfast, dinner latency were 87.3±75.2, 99.6±65.6 min, respectively. Average meals/day were 3.0±0.5. Meal skipping was reported in 3% (n=3) of women and nighttime eating in 35% (n=35). Most neonates had normal BMI/age (88%, n=88). Compared to those who did not, mothers engaged in nighttime-eating had infants with higher %FM (p=0.019). Regression models (R 2 ≥0.308, p≤0.001) showed that nighttime eating was positively associated with %FM (B: 2.7, 95%CI: 0.32-5.16). When analyzing women without complications/medications (n=80), nighttime eating was associated with higher FM (%FM, B: 3.24 (95%CI: 0.59-5.88); kgFM, B: 0.20 (95%CI: 0.003-0.40); FMI, B: 0.54 (95%CI: 0.03-1.05)). Infant sex and weight (6 months) were significant, while maternal obesity, pregnancy complications/medications, parity, energy intake, birth-BMI/age, and EBF were not. Conclusions: Maternal nighttime eating is associated with higher adiposity in 6-month infants.